Iqbal kabbe islami bhabdhara - Abdullah, Mohammad (Dhaka : University Grants Commision, 2006)
Language and Literature
Keywords: Iqbal kabbo; Islam; Tawhid; Qur'an; Islamic thought; Islam in Iqbal's poetry